Achalasia: new perspectives on an old disease. Issue 1 (January 2016) - Gyawali, C. P.
Abstract: Achalasia is defined by esophageal outflow obstruction from abnormal relaxation of the lower esophageal sphincter (LES) due to deranged inhibitory control. In genetically predisposed individuals, an autoimmune response to an unknown inciting agent, perhaps a viral infection, results in inflammation and sometimes loss of myenteric plexus ganglia and neurons. The net result is varying degrees of inhibitory dysfunction, at times associated with imbalanced and exaggerated excitatory function, with manometrically distinct achalasia phenotypes on high resolution manometry. There is new evidence in the current issue of this Journal suggesting that type 1 achalasia, with esophageal outflow obstruction and absent esophageal body contractility, is an end‐stage phenotype from progression of type 2 achalasia, which is characterized by panesophageal compartmentalization of pressure in the untreated patient, and partial recovery of peristalsis after treatment. Esophageal outflow obstruction with premature peristalsis (type 3 achalasia) or intact peristalsis may result from plexitis in the myenteric plexus but can also be encountered in other settings including chronic opioid medication usage and structural processes at the esophagogastric junction and distally. In most instances when idiopathic esophageal outflow obstruction is confirmed, some form of pharmacologic manipulation or disruption of the LES provides durable symptom relief. This review will focus on current understanding of pathophysiology, diagnosis, and principles of management of achalasia in light of emerging literature on the topic. Abstract : New research has added important new perspectives on the pathophysiology, diagnosis, and management of achalasia. In particular, clinical relevant subtypes have been defined with the use of high resolution manometry, and histopathologic differences between these subtypes are emerging. Structural obstruction at the esophagogastric junction, opioid medication usage, and neoplasia can result in manometric patterns similar to that seen with achalasia spectrum disorders.